A Ten-year Retrospective of General Practitioner Team Construction in China - ZHU Xuebo, DAI Haojie, LIN Jin (Zhongguo quanke yixue, 2024)
Background General practitioners (GPs) are an indispensable part of primary health care system in China and the implementation of the "Healthy China" strategy. In the past decade, the number of GPs in China has developed rapidly. Objective To summarize the experience and achievements of GP team construction from 2012 to 2022 (nearly ten years) , analyze the existing difficulties and deficiencies, and provide reference for the subsequent construction of GP team in China. Methods With the help of Donabedian model, policy support, capital investment and base construction were selected as the evaluation indicators of structural design process based on the SMART principle, the process quality was focused from two perspectives of standardized training of residents (referred to as standardized training) and job transfer, the construction of GP team in central and western China. The team size, structure, job satisfaction, resignation intention and career development opportunity were considered as the main analysis dimensions. The data were mainly obtained from Chinese government website and CNKI from 2012-01-01 to 2022-12-31, as well as Health Statistical Yearbook 2012-2022. Results In the past decade, the structural design of the construction of GP team in China has been continuously optimized and improved, and the supporting facilities such as capital investment and base construction have been closely implemented. The policy end of process has responded to the practical needs with dynamic adjustments, the standardization of relevant systems for standardized training and job transfer has steadily improved, and the construction of GP team in the central and western regions has been strengthened year by year. Regional differences in the effectiveness of team building still exist, and some problems need to be solved. Conclusion Existing human resource statistics on GP cannot accurately measure the human resource supply for GP team in China, and the construction of team stability needs to be further improved. It is recommended to continuously promote the stability construction of the GP team focusing on enhancing career attractiveness, improve the stability of the whole cycle of training, employment and career development, and jointly promote the stability of GP team.